Reply to “Correspondence: Androgen receptor mRNA in glioblastoma: a reliable marker of tumor burden or a statistical artefact?” - Larysa Liubych; Lorenz Hahn; Raja Hollnagel; Maria Karolin Streubel; Deepak Ailani; Jan Leppert; Harald Krenzlin; Jakob Matschke; Celina Soltwedel; Nicole Borgardt; Susanne Behling; Oksana Zemskova; et al. (Molecular Biology Reports, 2026)

Androgen receptor expression in glioblastoma: molecular profiling and association with tumor burden - Larysa Liubych; Lorenz Hahn; Raja Hollnagel; Maria Karolin Streubel; Deepak Ailani; Jan Leppert; Harald Krenzlin; Jakob Matschke; Celina Soltwedel; Nicole Borgardt; Susanne Behling; Oksana Zemskova; et al. (Molecular Biology Reports, 2026)

Signal and feature reconstruction in structural health monitoring under varying environmental conditions - Lizzie Neumann; Philipp Wittenberg; Alexander Mendler; Jan Gertheiss (Engineering Structures, 2026)

Development and analysis of a SmPC-based machine-readable dataset of contraindications for clinical decision support and real-world data analysis - Miriam Schechner; Wahram Andrikyan; Thomas Bauerdick; Theresa Terstegen; Louisa Redeker; Martin Federbusch; Katrin Farker; Alexander Strübing; Florian Schmidt; Petra Thürmann; Sven Schmiedl; Hanna M. Seidling; et al. (European Journal of Clinical Pharmacology, 2026)
Purpose Unrecognized contraindications pose risks for adverse drug reactions, hospitalizations or death. Clinical decision support systems (CDSS) aim to mitigate medication-related harm, particularly originating from contraindications. However, many CDSS provide limited benefit, as they focus largely on singular risk situations such as drug-drug interactions and often generate alerts of limited clinical relevance. Comprehensive integration of contraindications into CDSS may support more clinically meaningful alerts. The aim of this work was the development and analysis of machine-readable contraindication lists, including drug-clinical condition, drug-kidney function and drug-drug (group) contraindications, for integration into CDSS and real-world data analysis. Methods We extracted and operationalized contraindications, based on Summaries of Product Characteristics (SmPCs), of the 688 most prescribed drugs in Germany, leveraging common medical coding systems. Moreover, we analyzed extracted contraindications based on operationalizability, overall frequency and frequencies within different contraindication categories. Results In total, we extracted 4676 contraindications, of which 2129 (45.5%) were deemed operationalizable. Of these 2129 contraindications, 1652 (77.6%) were attributed to drug-clinical condition, 83 (3.9%) to drug-kidney, 140 (6.6%) to drug-drug group and 254 (11.9%) to drug-drug. The most frequently mentioned contraindicated risk situations were ‘severe liver insufficiency’ ( n = 74, 3.5%), ‘pregnancy’ ( n = 66, 3.1%), ‘MAO-inhibitors’ ( n = 44, 2.1%), and ‘shock’ ( n = 44, 2.1%). Conclusion Our results show, that drug-clinical condition contraindications are listed far more frequently in SmPCs than other contraindication categories. Focusing on clinical condition-related contraindications within CDSS could improve the detection of clinically relevant contraindications in routine data and enhance medication safety. The clinical applicability is currently being evaluated in the INTERPOLAR study.

Producing food from CO2 using microorganisms: Lots to do, little to lose! - Steven Minden; Alexander Grünberger; Ulrike van der Schaaf; Anke Neumann; Christine Rösch; Jörg Sauer; Anne-Kristin Kaster (Trends in Food Science & Technology, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Assessment of climate extremes at the regional scale during the last millennium using an annually resolved stalagmite record - Tobias Kluge; Philipp Holz; Thomas Neumann; Elisabeth Eiche; Maximilian Schuh; Norbert Frank; Ronny Friedrich; Alexander Land; Mario Trieloff; Axel K. Schmitt (Earth and Planetary Science Letters, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Auf dem Weg zu besseren Wasserstand-Durchfluss-Beziehungen - Henning Oppel; Juliane Neumann; Benjamin Mewes; Alexander Hartung (WASSERWIRTSCHAFT, 2023)

Air pollution exposure during pregnancy and childhood, APOE ε4 status and Alzheimer polygenic risk score, and brain structural morphology in preadolescents - Esmée Essers; Anne-Claire Binter; Alexander Neumann; Tonya White; Silvia Alemany; Mònica Guxens (Environmental Research, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Advancing Ocean Governance in Marine Regions Through Stakeholder Dialogue Processes - Laura Weiand; Sebastian Unger; Julien Rochette; Alexander Müller; Barbara Neumann (Frontiers in Marine Science, 2021)
The poor state of the ocean and the transboundary nature of the marine environment require bold action by States coordinated across sectors and territorial boundaries in order to deal with the manifold challenges the ocean is facing—and with it humankind. Cooperation and coordination among States and stakeholders in marine regions have proven to be important levers for policy implementation and to strengthen ocean governance, yet remain challenging. Transparent and engaging stakeholder dialogue processes have the potential to provide guidance for the necessary transformation toward ocean sustainability and support the attainment of Sustainable Development Goal (SDG) for the ocean, SDG 14 and other interlinked ocean-related targets. The aim of this study is to review the challenges and opportunities of current collaborative efforts, namely multi-stakeholder dialogue and exchange processes, within and between marine regions to accelerate transformative action, contributing to these global goals. This paper builds on knowledge co-production and collaborative governance literature, and reviews experiences by stakeholders with ocean-related science-policy interfaces in an effort to strengthen regional ocean governance. As an exemplary case of such interfaces, this study assesses the Marine Regions Forum, a newly established inclusive dialogue and exchange platform for diverse actors from marine regions that aims to provide an informal space for joint learning and support regional action and international governance processes alike. Employing latent content analysis of interviews with experts, critical common barriers that hamper current collaborative efforts amongst stakeholders in marine regions are identified, such as fragmented governance frameworks, power and resource imbalances, and lack of meaningful stakeholder engagement. Pathways to address these challenges, such as through common goal orientation, contextualisation, inclusivity, trust building and meaningful continuous interactions are also identified. This paper concludes by discussing the value added of transparent and inclusive collaborative processes in the transformation of ocean governance toward achieving sustainability.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: the importance of private collections - Carolin Haug; Jelle W. F. Reumer; Joachim T. Haug; Antonio Arillo; Denis Audo; Dany Azar; Viktor Baranov; Rolf Beutel; Sylvain Charbonnier; Rodney Feldmann; Christian Foth; René H. B. Fraaije; et al. (PalZ, 2020)

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: Myanmar amber - Joachim T. Haug; Dany Azar; Andrew Ross; Jacek Szwedo; Bo Wang; Antonio Arillo; Viktor Baranov; Julia Bechteler; Rolf Beutel; Vladimir Blagoderov; Xavier Delclòs; Jason Dunlop; et al. (PalZ, 2020)

Super Deep Boring Technology - Alexander Bolonkin; Joseph Friedlander; Shmuel Neumann (Geotechnical and Geological Engineering, 2020)

Relationships between performance test and match-related physical performance parameters - Stefan Altmann; Maximilian Kuberczyk; Steffen Ringhof; Rainer Neumann; Alexander Woll (German Journal of Exercise and Sport Research, 2018)

Formation of Si-Al-Mg-Ca-rich zoned magnetite in an end-Permian phreatomagmatic pipe in the Tunguska Basin, East Siberia - Else-Ragnhild Neumann; Henrik H. Svensen; Alexander G. Polozov; Øyvind Hammer (Mineralium Deposita, 2017)

Climate change effects on denitrification and associated avoidance costs in three Baltic river basin - coastal sea systems - Alexander Allin; Gerald Schernewski; Rene Friedland; Thomas Neumann; Hagen Radtke (Journal of Coastal Conservation, 2017)

The effect of skin fatty acids on Staphylococcus aureus - Yvonne Neumann; Knut Ohlsen; Stefanie Donat; Susanne Engelmann; Harald Kusch; Dirk Albrecht; Michael Cartron; Alexander Hurd; Simon J. Foster (Archives of Microbiology, 2015)

IKV-Nachrichten - Wolf Günther Koch; Alexander Wolodtschenko; Ulrich Freitag; Joachim Neumann; Joachim Dammhain (KN - Journal of Cartography and Geographic Information, 1997)